SAKῙNAH, MAWADDAH DAN RAḤMAH DALAM PERHUBUNGAN SUAMI ISTERI: ANALISIS LITERATUR: Sakīnah, Mawaddah and Raḥmah in Husband-Wife Relationship: A Literature Review - Musthapar, Nur Faezah; Hj Azahari, Raihanah; Ahmad, Bahiyah (Jurnal Syariah, 2020)
One of the purposes of marriage is to create a sakīnah (tranquil), mawaddah (affectionate) and raḥmah (merciful) life among a husband, a wife and their children. The sakīnah, mawaddah and raḥmah’s life, however, does not come in handy with the marriage. It must be striven by both men and wives during their marriage. Sakīnah, mawaddah and raḥmah are the goals of a marriage. A true understanding of these three concepts can restore the troubled marriage’s relationship. There are various studies on the concepts of sakīnah, mawaddah and raḥmah. This article will examine these three concepts in various forms such as academic books, dissertations, theses and journal articles. Generally this theme study discusses the three concepts in detail with detailing the scope of the marriage’s relationship and commenting on how spouses apply these three concepts in their current relationship. This study found that there is a need to conduct specific research on this topic to fill in the gaps associated with Muslim family research. This is to provide a comprehensive study and analysis of understanding of the three terminologies relevant for application in contemporary life.